Formation of Resin-Rich Zones in Composites Processing - Dong, Chensong; Tsai, Tze (Trans Tech Publications Inc, 2010)
Resin-rich zones are a common phenomenon in liquid composite molding processes. These resin-rich zones cause unwanted residual stress and deformation, and part-to-part variation, and thus they need to be studied in the design of composite structures. An experimental study on the formation of resin-rich zones in angled composite parts is presented in this paper. Two open-channel mold sets were designed and fabricated. Fiber preforms were loaded into these molds and the gaps formed were visually inspected by a microscope. The influences of corner radius, fiber volume fraction, enclosed angle, and stacking sequence were investigated, and significant factors affecting gap thickness were identified by Design of Experiments (DOE). It can be concluded from the experimental results that: 1) Fiber volume fraction is the most significant factor affecting gap thickness. Gap thickness is inversely proportional to fiber volume fraction; 2) Gap thickness is inversely proportional to radius; 3) The gap thickness of unidirectional preforms is larger than that of the cross-ply preforms.